Vulvovaginal candidiasis therapy in reproductive age women - Т. Г. Романенко; О. М. Суліменко (Publishing House TRILIST, 2020)
Objective of the study: was to determine the effectiveness of complex therapy with Fusys® (fluconazole, 150 mg tablets) in combination with Clofan® (clotrimazole, vaginal suppositories 500 mg) in the treatment of acute vulvovaginal candidiasis (VVC). Materials and methods. 38 patients in the age of 22 to 42 were examined for acute VVC. C. albicans fungi were causative agent of VVC in all women. After vaginal candidiasis diagnosis was confirmed, all patients were prescribed oral systemic fluconazole 150 mg (Fusys®) once in combination with a single vaginal administration of Clofan® (clotrimazole, vaginal suppositories 500 mg) for acute VVC treatment. At the same time, they warned of the need to treat a partner (Fusys® gel was prescribed). Effectiveness of treatment was evaluated after 3; 7 and 30 days after therapy. Results. All study participants noted a decrease in the severity of itching and intensity of discharge from the genital tract on the third day after therapy. Clinical symptoms of VVC completely disappeared in 35 (92.1%) women by the end of the seventh day after treatment. Microscopic and cultural examination revealed no Candida fungi in 31 (81.6%) patients. The rest of the women who had candidiasis again were treated by once prescribed oral Fusys® (150 mg) in combination with a single vaginal administration of Clofan® suppositories (500 mg). Repeated microscopic and culture studies carried out after 7 days showed no fungi in these patients. Conclusion. The effectiveness of VVC complex therapy in the study was 92.1%. The results indicate high clinical and microbiological efficacy of complex therapy in combination with fluconazole (Fusys®) and clotrimazole Clofan® for the VVC treatment in women of reproductive age